Percutaneous Tibial Nerve Stimulation in Chronic Post-Surgical Anorectal Pain: A Case Report - Pacheco,Marta (2022)
Abstract Introduction: Anorectal pain is a symptom with a negative impact on quality of life and it can sometimes develop into a chronic pain syndrome. Structural anorectal pain is treated according to the underlying pathology. In situations of chronic post-surgical pain that is refractory to conventional therapeutic approaches, percutaneous tibial nerve stimulation (PTNS) is an option. PTNS is a neurostimulation technique used in the treatment of lower urinary tract dysfunction. There has been increasing evidence of its benefits for improving other conditions, such as chronic pelvic pain (CPP) and faecal incontinence (FI). Case Presentation: We report a case of a 45-year-old woman with chronic post-surgical anorectal pain (CPAP) treated with PTNS. The patient reported a consistent and dramatic decrease in both the frequency and intensity of pain, assessed by the Brief Pain Inventory (BPI). A decrease in the pain interference with mood, normal work, and walking/mobility was also noted, as evaluated by BPI and EQ-5D-3L questionnaires. Discussion: Neuromodulation treatments have been reported as effective for anorectal pain, but reports on the use of PTNS are rare. The tibial nerve is easily accessible and provides an optimal site for neurostimulation without the need of an operating room or anaesthesia. The overall improvement observed in this case of chronic anorectal pain suggests a potential new area of research for PTNS.